The Intention-Behavior gap in Ethical Consumption: Mediators, Moderators and Consumer Profiles Based on Ethical Priorities - Casais, Beatriz; Faria, Joana (Journal of macromarketing, 2022)
Ethical consumers do not always convert their beliefs into purchasing decisions and the impact of influencing variables on the intention-behavior (I-B) gap in ethical consumption remains unresearched. The answers of 364 respondents expressing their intentions regarding ethical consumption and of 346 having ever purchased ethically show that the I-B relationship is mediated by Plans and Habits and moderated by Commitment and Sacrifice, although this was not a full moderation. This study identifies four profiles of ethical consumers, considering the hierarchy of ethical choices and the fact that ethical issues are prioritized as primary and secondary concerns. This paper is the first to measure the mediation and moderation variables regarding the I-B gap in ethical consumption, discussing intervention and priorities to close the gap: promoting ethical consumption as a social norm, expanding the distribution of prioritized ethical products, and mitigating the barriers that entail sacrifices to purchasing ethically.